IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN PPKN KELAS XI MIPA 5 SMAN 1 PONTIANAK - Desky, Handoko; Sulistyarini, Sulistyarini; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the implementation of Character building/Education in PPKn Subject to Class XI MIPA 5 SMA 1 Pontianak. The research method used is descriptive study in form of qualitative research. The data sources of this study are PPKn teachers and student of class XI MIPA 5. Data collection techniques used are observation, interview and documentation. The analysis in this study is presented in a descriptive qualitative research with 5 people as the main informants. The results of this study indicate that the planning of learning made by the teacher for completeness of the lesson plan components starting from school identity, subject identity, class / semester, subject matter, time allocation, learning objectives, basic competencies and indicators of achievement of competencies, learning materials, learning methods, learning media, learning resources, learning steps and assessment of learning outcomes, while for character values that appear as many as 12 character values namely religious, national spirit, discipline, love to read, independent, curiosity, communicative, responsibility, honest , tolerance, creative and appreciating the achievements in learning planning. The implementation of character education carried out by teachers is by implementing exemplary, routine activities, conditioning and spontaneous activities.Â Keywords: Character Building, Implementation, PPKn